Impacts of increased CO2 and temperature upon DMSP production in the cold-water coral, Lophelia pertusa, from short-term experiments carried out on cruise D366/7. - Burdett, Heidi; Carruthers, Madeline; Donohue, Penelope; Wicks, Laura; Hennige, Sebastian; Roberts, John Murray; Kamenos, Nicholas A (British Oceanographic Data Centre, Natural Environment Research Council, 2014)
Dimethylsulphoniopropionate (DMSP), and its breakdown product dimethylsulphide (DMS), are putative antioxidants that may be accumulated by invertebrates via their food or symbionts; recent research suggests that some invertebrates may also be able to synthesise DMSP. This dataset is the first to provide information on the impact of high temperature (12degC) and high CO2 (817 ppm) on intracellular DMSP in the cold water coral Lophelia pertusa from the Mingulay Reef Complex, Scotland (56deg49'N, 07deg23'W). The experiment was conducted during the 'Changing Oceans Expedition' in June 2012, aboard the Royal Research Ship James Cook (cruise JC073). Coral colonies were obtained using the Holland-1 Remotely Operated Vehicle (ROV) 180 m below chart datum at the Mingulay Reef Complex and maintained for 10 days in one of four treatments (control, high temperature, high CO2, high temperature+CO2). Samples for coral intracellular DMSP and mesocosm water DMS+DMSP were fixed on-board and transported to the University of Glasgow for subsequent analysis by gas chromatography.